Compromite subcultura criminală educația și dezvoltarea armonioasă a minorilor? [Articol] - Samoilenco, Victor (CEP USM, 2022)
From all of the social anomies existing in the Republic of Moldova, the criminal subculture represents the most serious social danger. Children and young people in particular have a high risk of subculturalization, fact that is due to their age characteristics. The poor level of development of critical thinking, in the case of children, it is decisive when they adopt antisocial solutions. To decrease the level of adherence to that subculture, the state must adopt preventive measures and combative measures in equal measure. The incrimination of some antisocial acts such as the indoctrination of children can also represent a suitable option. Unfortunately, most prophylactic measures are taken in the detention environment, the extra-prison environment being ignored. It is disregarded that outside the bars, this criminal scourge is also very well developed. This fact proves to us that preventive measures must also be taken within the extra-prison society.
Keywords: subculturalization; child; minors; subcultura criminală